Analisis Dampak Bahasa Gaul pada Mahasiswa Ilmu Ekonomi B Unimed Terhadap Bahasa Indonesia Masa Kini - Angelina Rolas Olivia Naibaho; Joan Agus Sirait; Raymond Panuturi Siboro; Fitriani Lubis (Universitas Kristen Indonesia Toraja, 2024)
The research at Universitas Negeri Medan focuses Use of slang between students in the Economics class of 2022, utilizing a survey method. The results reveal significant impacts of slang, both positive and negative, particularly concerning the proper use of the Indonesian language. Factors such as popular culture and globalization contribute to these effects, with the negative impact manifesting as a decline in overall proficiency in the Indonesian language. This study elucidates student perspectives, emphasizing the need to raise their awareness of it importance of using Indonesian properly. Recommendations include concrete steps, such as broadcasting pride demonstrations in Indonesian on social media, to strengthen the use of formal language and prevent the lossof Indonesian.